Tidsrummet for Hamborgkulturens bosættelse ved Jelssøerne kommenteret gennem forsøg på flintsammensætning - Pedersen, Jesper Borre (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
As the Weichselian glaciation came to an end, the Fennoscandian ice sheet retreated and left behind young moraine landscapes, today referred to as southern Scandinavia. During this so-called Last Glacial-Interglacial Transition humans began to colonise the recently de-glaciated area with the earliest colonisation attempt taking place during the Bølling/ Meiendorf chronozone (G I-1e). These pioneer settlers of the region brought with them a lithic repertoire of the Hamburgian Havelte tradition and are in Denmark known from sites separated into two somewhat delineated occupation areas, one of which is in southern Jutland at the Jels Lakes. The sites within this settlement pocket are similar in several aspects, and interpretations of these sites making out one concurrent occupation have previously been proposed, yet rarely followed up upon. In this paper the question of contemporaneity between the two sites is revisited. With relevance to the rhythms of settlement or, indeed, of contemporaneity, within the Hamburgian micro-region at Jels, first attempts at refitting lithic material from these sites have been conducted. Impressions are here presented and future perspectives assessed.